A Series of Bisamide‐Substituted Diacetylenes Exhibiting a Terminal Alkyl Odd/Even Parity Effect on Mechanoactivated Photopolymerization. Issue 11 (21st January 2021) - Qi, Jiajun; Kim, Yuna; Takahashi, Kiyonori; Aoki, Ken'ichi; Hisaki, Ichiro; Nakamura, Takayoshi; Tamaoki, Nobuyuki
Abstract: Diacetylene derivatives exhibit solid‐state polymerization to polydiacetylene initiated by UV light or γ‐ray irradiation. The activation of the photopolymerization relies on the monomer diynes arrangement. Recently, it has been demonstrated that the first mechanoresponsive bisamide substituted diacetylenes (DAs) show dramatic switching from light‐inert to light‐reactive states at a given pressure. The origin of this unique phenomenon was apparently related to the pressure‐sensitive crystalline transition in DAs, but the molecular mechanism remains elusive. To obtain more insight, herein a series of DAs with varying terminal alkyl spacer length is presented, and their molecular structural effect on the intermolecular hydrogen bonding and steric repulsion is examined. In pristine states, even‐parity DAs were inactive upon UV irradiation ( λ =254 nm) unless external pressure was applied. By contrast, odd‐parity DAs were easily polymerized upon UV irradiation without pressure application. However, the pressure‐induced crystalline phase transition exhibiting photopolymerization was valid for all DAs regardless of their alkyl spacer length. A systematic investigation revealed that the terminal alkyl spacer length, especially its odd/even parity plays a key role in determining the intrinsic intermolecular hydrogen‐bonding nature of DA crystals and the resultant molecular packing. In addition, the relevant thermochromic behavior was also observed from photopolymerized polydiacetylenes. Abstract : Odd versus even : A series of bisamide‐substituted diacetylenes with varying terminal alkyl spacer length showed unique pressure‐induced photopolymerizability. The odd or even parity of the terminal alkyl gave a light‐active and light‐inert pristine state, respectively. It is revealed that the intermolecular hydrogen bonds were highly influenced by the terminal alkyl parity, resulting in the different crystalline packings and photopolymerization properties.